2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Buchholz, Verena Nadine; Kornhuber, Johannes; Lenz, Bernd (Early Human Development, 2023)
Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents (M = 13.32 years, SD = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans (M = 7.87 years, SD = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 2D:4D ratio; Alcohol; Androgen load; Biomarker; Construct validity; Heritability; Nicotine; Pregnancy risk; Prenatal; Retest reliability; Stability; Testosterone exposure

Additive sex-specific influence of common non-synonymous DISC1 variants on amygdala, basal ganglia, and white cortical surface area in healthy young adults - Mühle, Christiane; Kreczi, Jakob; Rhein, Cosima; Richter-Schmidinger, Tanja; Alexopoulos, Panagiotis; Dörfler, Arnd; Lenz, Bernd; Kornhuber, Johannes (Brain Structure & Function, 2017)
The disrupted-in-schizophrenia-1 (DISC1) gene is known for its role in the development of mental disorders. It is also involved in neurodevelopment, cognition, and memory. To investigate the association between DISC1 variants and brain morphology, we analyzed the influence of the three common non-synonymous polymorphisms in DISC1 on specific brain structures in healthy young adults. The volumes of brain regions were determined in 145 subjects by magnetic resonance imaging and automated analysis using FreeSurfer. Genotyping was performed by high resolution melting of amplified products. In an additive genetic model, rs6675281 (Leu607Phe), rs3738401 (Arg264Gln), and rs821616 (Ser704Cys) significantly explained the volume variance of the amygdala (p = 0.007) and the pallidum (p = 0.004). A higher cumulative portion of minor alleles was associated with larger volumes of the amygdala (p = 0.005), the pallidum (p = 0.001), the caudate (p = 0.024), and the putamen (p = 0.007). Sex-stratified analysis revealed a strong genetic effect of rs6675281 on putamen and pallidum in females but not in males and an opposite influence of rs3738401 on the white cortical surface in females compared to males. The strongest single association was found for rs821616 and the amygdala volume in male subjects (p < 0.001). No effect was detected for the nucleus accumbens. We report-to our knowledge-for the first time a significant and sex-specific influence of common DISC1 variants on volumes of the basal ganglia, the amygdala and on the cortical surface area. Our results demonstrate that the additive model of all three polymorphisms outperforms their single analysis.
EVALuna2:33147

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

Alpha-Synuclein RNA Expression is Increased in Major Depression - Rotter, Andrea; Lenz, Bernd; Pitsch, Ruben; Richter-Schmidinger, Tanja; Kornhuber, Johannes; Rhein, Cosima (International Journal of Molecular Sciences, 2019)
Alpha-synuclein (SNCA) is a small membrane protein that plays an important role in neuro-psychiatric diseases. It is best known for its abnormal subcellular aggregation in Lewy bodies that serves as a hallmark of Parkinson's disease (PD). Due to the high comorbidity of PD with depression, we investigated the role of SNCA in patients suffering from major depressive disorder (MDD). SNCA mRNA expression levels were analyzed in peripheral blood cells of MDD patients and a healthy control group. SNCA mRNA expression was positively correlated with severity of depression as indicated by psychometric assessment. We found a significant increase in SNCA mRNA expression levels in severely depressed patients compared with controls. Thus, SNCA analysis could be a helpful target in the search for biomarkers of MDD.
CRIS-Team Scopus Importer:2019-05-17
Keywords: alpha-synuclein; Hamilton Scale of Depression; major depression; SNCA

Alternative splicing of SMPD1 coding for acid sphingomyelinase in major depression - Rhein, Cosima; Reichel, Martin; Kramer, Marcel; Rotter, Andrea; Lenz, Bernd; Mühle, Christiane; Gulbins, Erich; Kornhuber, Johannes (Journal of Affective Disorders, 2017)
BACKGROUND: Major depressive disorder (MDD) is a psychiatric disorder characterized by key symptoms that include depressed mood and a loss of interest and pleasure. A recently developed pathogenic model of MDD involves disturbed neurogenesis in the hippocampus, where the acid sphingomyelinase (ASM)/ceramide system plays an important role and is proposed as a molecular target for antidepressant action. Because alternative splicing of SMPD1 mRNA, coding for ASM, is relevant for the regulation of ASM enzymatic activity, we investigated the frequency of alternatively spliced ASM isoforms in peripheral blood cells of MDD patients versus healthy controls. METHODS: Because the full-length transcript variant 1 of SMPD1 (termed ASM-1) is the only known form within the splicing pattern that encodes an enzymatically fully active ASM, we determined a fraction of splice isoforms deviating from ASM-1 using PCR amplification and capillary electrophoresis with laser-induced fluorescence analysis. RESULTS: ASM alternative splicing events occurred significantly less frequently in MDD patients compared to healthy subjects. After 5 days of antidepressant treatment, the frequency of alternatively spliced ASM isoforms decreased in those patients who were treated with a functional inhibitor of ASM activity (FIASMA) but remained constant in MDD patients treated with other antidepressant drugs. This effect was more pronounced when healthy male volunteers were treated with the FIASMAs fluoxetine or paroxetine, in contrast to a placebo group. LIMITATIONS: Patients were treated with different antidepressant drugs, depending on individual parameters and disease courses. CONCLUSIONS: This study shows that the ASM alternative splicing pattern could be a biological target with diagnostic relevance and could serve as a novel biomarker for MDD.
EVALuna2:33501

Association of a CAMK2A genetic variant with logical memory performance and hippocampal volume in the elderly - Rhein, Cosima; Mühle, Christiane; Lenz, Bernd; Richter-Schmidinger, Tanja; Kogias, Georgios; Boix, Fernando; Lourdusamy, Anbarasu; Dörfler, Arnd; Peters, Oliver; Ramirez, Alfredo; Jessen, Frank; Maier, Wolfgang; et al. (Brain Research Bulletin, 2020)
Calcium/Calmodulin-dependent kinase alpha (αCaMKII) has been shown to play an essential role in synaptic plasticity and in learning and memory in animal models. However, there is little evidence for an involvement in specific memories in humans. Here we tested the potential involvement of the αCaMKII coding gene CAMK2A in verbal logical memory in two Caucasian populations from Germany, in a sample of 209 elderly people with cognitive impairments and a sample of 142 healthy adults. The association of single nucleotide polymorphisms (SNPs) located within the genomic region of CAMK2A with verbal logical memory learning and retrieval from the Wechsler Memory Scale was measured and hippocampal volume was assessed by structural MRI. In the elderly people, we found the minor allele of CAMK2A intronic SNP rs919741 to predict a higher hippocampal volume and better logical memory retrieval. This association was not found in healthy adults. The present study may provide evidence for an association of a genetic variant of the CAMK2A gene specifically with retrieval of logical memory in elderly humans. This effect is possibly mediated by a higher hippocampal volume.
CRIS-Team Scopus Importer:2020-05-22
Keywords: adults; CAMK2A; elderly; hippocampus; logical memory; αCaMKII

Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

Association of testosterone and BDNF serum levels with craving during alcohol withdrawal - Heberlein, Annemarie; Lenz, Bernd; Opfermann, Birgitt; Groschl, Michael; Janke, Eva; Stange, Katrin; Groh, Adrian; Kornhuber, Johannes; Frieling, Helge; Bleich, Stefan; Hillemacher, Thomas (Alcohol, 2016)
Preclinical and clinical studies show associations between testosterone and brain-derived neurotrophic growth factor (BDNF) serum levels. BDNF and testosterone have been independently reported to influence alcohol consumption. Therefore, we aimed to investigate a possible interplay of testosterone and BDNF contributing to alcohol dependence. Regarding possible interplay of testosterone and BDNF and the activity of the hypothalamic pituitary axis (HPA), we included cortisol serum levels in our research. We investigated testosterone and BDNF serum levels in a sample of 99 male alcohol-dependent patients during alcohol withdrawal (day 1, 7, and 14) and compared them to a healthy male control group (n = 17). The testosterone serum levels were significantly (p < 0.001) higher in the patients' group than in the control group and decreased significantly during alcohol withdrawal (p < 0.001). The decrease of testosterone serum levels during alcohol withdrawal (days 1-7) was significantly associated with the BDNF serum levels (day 1: p = 0.008). In a subgroup of patients showing high cortisol serum levels (putatively mirroring high HPA activity), we found a significant association of BDNF and testosterone as well as with alcohol craving measured by the Obsessive and Compulsive Drinking Scale (OCDS). Our data suggest a possible association of BDNF and testosterone serum levels, which may be relevant for the symptomatology of alcohol dependence. Further studies are needed to clarify our results.
EVALuna2:23779

Association of Testosterone Levels and Steroid 5-Alpha-Reductase 2 Polymorphisms with Opioid Craving - Janke, Eva; Groh, Adrian; Mühle, Christiane; Dürsteler-Macfarland, Kenneth M.; Wiesbeck, Gerhard A.; Kornhuber, Johannes; Jahn, Kirsten; Groeschl, Michael; Lichtinghagen, Ralf; Frieling, Helge; Bleich, Stefan; Hillemacher, Thomas; et al. (Neuropsychobiology, 2020)
Background/Aims: Opioid dependence is a severe disease which is associated with a high risk of relapse, even in cases of successful withdrawal therapy. Studies have shown alterations of the hypothalamic-pituitary-gonadal axis in opioid-dependent patients, such as decreased testosterone serum levels in affected males. Sex hormones and the steroid 5-alpha-reductase 2 (SRD5A2) V89L polymorphism are associated with craving during alcohol withdrawal, but little is known about their impact on symptomatology of opioid dependence. Methods: In this study, we analyzed 2 independent male cohorts of opioid-dependent patients for possible alterations in testosterone serum levels compared to non-opioid-dependent controls. In one of the cohorts, we additionally investigated associations of testosterone serum levels and 3 SRD5A2 polymorphisms with symptoms of opioid dependence, measured by the Heroin Craving Questionnaire (HCQ). Results: In the patient groups, we found significantly decreased testosterone serum levels compared to the control groups. Furthermore, we found significant associations of both the testosterone serum levels and the SRD5A2 V89L polymorphism with opioid craving assessed by the HCQ. Conclusion: Our data show a possible role of testosterone metabolism in opioid dependence, which may be relevant for the establishment of future treatment strategies.
CRIS-Team Scopus Importer:2020-07-31

Basic Human Body Dimensions Relate to Alcohol Dependence and Predict Hospital Readmission - Lenz, Bernd; Köllner, Martin; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes (Journal of Clinical Medicine, 2019)
Alcohol dependence is a severe mental illness and there is a need for more effective preventive and therapeutic strategies. Translational research suggests that intrauterine sex hormone exposure modulates the risk and course of alcohol dependence during adulthood. During development, sex hormones permanently shape sexually dimorphic body dimensions. Thus, these dimensions may provide insight into sex hormone organization. Here, we compared body measurements (absolute, relative to, and residualized on height) between 200 alcohol-dependent in-patients and 240 age-matched healthy control subjects and investigated how these measurements associate with the patients' prospective 12- and 24-month outcome. The results show that alcohol dependence is related to lower absolute, relative, and residualized body measurements for height and weight, head circumference, bitragion head arc, lip-chin distance, hip, thigh, and calf circumference, and foot length and breadth. In male alcohol-dependent in-patients, higher risk, shorter latency, and more alcohol-related readmissions were predicted by higher absolute, relative, and residualized thigh and calf circumferences. The second-to-fourth finger length ratio, a putative proxy for prenatal sex hormone organization, was not convincingly correlated with the body dimensions, suggesting that the results represent pubertal (or later) effects. The study's findings have implications for further research. The body measurements' high accessibility may facilitate the future transition into clinical settings.
CRIS-Team WoS Importer:2020-01-28

Bioimpedance Body Measures and Serum Lipid Levels in Masculine Depression - von Zimmermann, Claudia; Brückner, Lena; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is a main reason for suicide, and serum lipids are involved in both affective disorders and related suicidal behavior. Moreover, masculine depression has been suggested as a subtype of depression with an increased risk for suicide. Here, we studied the relationship between body measures, serum lipids, suicidal thoughts, and masculine depression. Methods: Depressed patients (44% women) were divided by a sex-separated median-split into a group of 81 “patients with masculine depression” (mean age ± standard error: 36.4 ± 1.6 years) and a group of 82 “patients with non-masculine depression” (age 45.7 ± 1.6 years) according to the Male Depression Risk Scale. We compared body measures, serum lipid levels, and past suicidal ideation between these groups and explored differences between these groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years). Results: Patients with masculine depression did not significantly differ from patients with non-masculine depression in any of the body measures, lipid markers, or suicidal thoughts. Compared to healthy controls, both patient groups showed significantly higher body fat (B[masculine depression] = 0.041 and B[non–masculine depression] = 0.050), lower high-density lipoprotein (HDL) cholesterol (B = –0.045 and –0.044), and a higher risk for suicidal thoughts (B = 3.927 and 2.663) than healthy controls. Suicidal thoughts were significantly associated with lower low-density lipoprotein (LDL)/HDL ratios (B = –0.455) in patients with depression and with higher LDL cholesterol levels (B = 0.020) in healthy controls subjects. Limitation: Correlational study design and focus on in-patients. Conclusion: In the studied cohort, masculine depression was not significantly associated with the analyzed parameters of body measures, serum lipids, or suicidal thoughts in in-patients with depression.
CRIS-Team Scopus Importer:2022-08-12
Keywords: body fat; cholesterol; masculine depression; serum lipids; suicidal behavior

Body mass index and craving predict 24-month hospital readmissions of alcohol-dependent in-patients following withdrawal - Weinland, Christian; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2019)
OBJECTIVE: Addictive alcohol drinking, craving, and overeating share common etiopathological mechanisms. We investigated whether body mass index (BMI) and craving predict outcome of alcohol-dependent in-patients. METHOD: The prospective study included 101 male and 72 female early-abstinent alcohol-dependent in-patients. Craving was quantified by Obsessive-Compulsive Drinking Scale (OCDS) scores. We documented alcohol-related readmissions over 24 months. RESULTS: In males, a higher BMI was associated with alcohol-related hospital readmission (median 26.1 vs. 23.1 kg/m2, P = .007) and correlated with more (ρ = 0.286, P = .004) and earlier readmissions (ρ = -0.256, P = .010). These associations were stronger in the subgroup of active smokers (n = 79; median 25.9 vs. 22.3 kg/m2, P = .005; ρ = 0.350, P = .002; ρ = -0.340, P = .002). BMI did not significantly predict outcome in females. Males with at least one readmission reported higher OCDS scores than those without (OCDS-total, OCDS-obsessive, OCDS-compulsive, P < .040), and the OCDS scores correlated with more readmissions (males: OCDS-total, OCDS-obsessive, OCDS-compulsive, ρ > 0.244, P < .014; females: OCDS-compulsive, ρ = 0.341, P = .003) and fewer days to first readmission (males: OCDS-total, OCDS-compulsive, ρ < -0.195, P < .050; females: OCDS-compulsive, ρ = -0.335, P = .004). The OCDS scores explained 9 to 19% of the relationship between BMI and outcome in males. CONCLUSION: BMI and craving are easily accessible outcome predictors of alcohol-related readmission following in-patient withdrawal treatment. They might be used to individualize relapse prevention in the future.
EVALuna2:211615

Body mass index and serum levels of soluble leptin receptor are sex-specifically related to alcohol binge drinking behavior - Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes; Weinland, Christian; Lenz, Bernd (Psychoneuroendocrinology, 2021)
Objective: Binge drinking is a highly prevalent behavior in adolescents and young adults and a risk factor to develop alcohol use disorder. Body mass index (BMI) and blood levels of leptin peptide and its soluble receptor have been implicated in alcohol use disorder; however, their role in binge drinking remains to be investigated. Method: We studied associations of BMI, serum levels of soluble leptin receptor (ObRe) and leptin as well as the free leptin index with binge drinking in 93 male and 99 female young adults. Results: In men, binge drinkers showed significantly higher BMI (kg/m2) than non-binge drinkers (23.67 vs. 22.08) and higher BMI correlated significantly with more severe binge drinking episodes (ρ = 0.251). In women, we found significantly higher ObRe (ng/ml) / BMI (kg/m2) values in binge drinkers than in non-binge drinkers (0.52 vs. 0.44) and ObRe/BMI values correlated significantly with more severe binge drinking episodes (ρ = 0.210). Conclusion: This study confirms that higher BMI associates with binge drinking in men and shows for the first time a role of ObRe/BMI in binge drinking in women. Our data emphasize the importance of further research in the ﬁeld of metabolic markers and implications in neurobiological processes of binge drinking.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alcohol binge drinking; Body mass index; Leptin; Soluble leptin receptor

CAGn repeat of the androgen receptor is linked to proopiomelanocortin promoter methylation-relevance for craving of male alcohol-dependent patients? - Muschler, Marc Andre Nicolas; Lenz, Bernd; Hillemacher, Thomas; Kraus, Cornelia; Kornhuber, Johannes; Frieling, Helge; Bleich, Stefan (Psychopharmacology, 2014)
Previous findings of the Franconian Alcoholism Research Studies showed that both the CAGn of the androgen receptor (AR) and the promoter methylation of the hypothalamic peptide proopiomelanocortin (POMC) were associated with craving of male alcohol-dependent patients.Based on the strong interactions between the hypothalamic-pituitary-gonadal (HPG) and the hypothalamic-pituitary-adrenal axis (HPA), this study investigated the relationships between the CAGn repeat of the AR, POMC promoter methylation and craving of male alcohol-dependent patients.This analysis covers 84 male patients with a diagnosis of alcohol dependence (DSM-IV). We sequenced the POMC gene promoter using bisulfite modified DNA to display the methylation status. Furthermore, we sequenced the CAGn repeat within exon 1 of the AR gene. Craving was quantified by the Obsessive Compulsive Drinking Scale.We found an inverse correlation between the number of CAGn repeats of the AR and the POMC methylation status in this study. Altogether, the POMC promoter methylation accounted for 33 % of the relationship between CAGn AR polymorphism and craving.This work shows that the AR and the POMC gene might functionally interact with each other and subsequently mediate craving in alcohol-dependent patients. The paper discusses different mechanisms which might underlie our findings involving sex hormones' and sex determining region of Y-gene's regulatory function on DNA-methyltransferase activity. In conclusion, the results give insight in the interaction between HPG and HPA axis. This study is a further step on the way to a better understanding of genetic and non-genetic factors underlying craving for alcohol.
EVALuna2:9197

Cloninger Type 2 Score and Lesch Typology Predict Hospital Readmission of Female and Male Alcohol-Dependent Inpatients During a 24-Month Follow-Up - Weinland, Christian; Braun, Birgit; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2017)
BACKGROUND: Relapse after detoxification treatment is a common problem in alcohol dependence. However, its prediction still lacks reliability. We here investigated whether the easily accessible clinical Cloninger and Lesch classifications predict alcohol-related hospital readmission following inpatient withdrawal treatment. METHODS: In this bicentric prospective clinical study, 67 female and 84 male alcohol-dependent inpatients were characterized according to the Cloninger items and the Lesch typology. The patients' records were followed for 24 months. Because of the well-established sex differences in alcohol dependence, we studied females and males separately. RESULTS: Overall, 54% of the female patients and 67% of the male patients sustained at least 1 alcohol-related hospital readmission during the follow-up. Readmission was related to a higher Cloninger type 2 score than nonreadmission (females, p = 0.007, males p = 0.044). In females, the Cloninger type 2 score correlated with the number of readmissions (ρ = 0.384, p = 0.001) and the days to first readmission (ρ = -0.333, p = 0.006). The effects were stronger in patients with age at onset of alcohol dependence over 25 years. We found gender dimorphisms concerning the Cloninger items. In female patients, the 4 Lesch subtypes differed in their risk (p = 0.010), the number (p = 0.040), and the days to first readmission (p = 0.031). Lesch type 1 was associated with an increased risk (OR = 4.83, p = 0.041) and Lesch type 2 with a reduced risk (OR = 0.07, p = 0.004). In addition, the number of previous inpatient alcohol withdrawals predicted the patients' outcomes (p < 0.05). CONCLUSIONS: The Cloninger type 2 score and the Lesch typology are promising tools for the prediction of alcohol-related readmissions. Our findings provide the basis to optimize relapse prevention in alcohol dependence.
EVALuna2:33401

Crossed Eye/Hand Laterality and Left-Eyedness Predict a Positive 24-Month Outcome in Alcohol-Dependent Patients - Weinland, Christian; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2019)
Background: Available predictors of hospital readmission following withdrawal in alcohol-dependent patients are limited. However, such parameters are needed to optimize individualized treatment strategies. This study investigated whether crossed eye/hand laterality, eyedness, and handedness may predict outcomes in alcohol dependence. Methods: The prospective study included 200 early-abstinent alcohol-dependent inpatients (n[males] = 113, n[females] = 87) and 240 control subjects (n[males] = 133, n[females] = 107). We assessed eyedness and handedness using the hole-in-the-card and Shimizu tests and documented alcohol-related readmissions over 12 and 24 months. Results: Crossed eye/hand laterality and left-eyedness were associated with a reduced risk for alcohol-related readmission (12-month: odds ratios [OR] = 0.41, p = 0.008, OR = 0.42, p = 0.004; 24-month: OR = 0.57, p = 0.097, OR = 0.47, p = 0.016), fewer median readmissions (12-month: 0 vs. 1, p = 0.005, 0 vs. 1, p = 0.005; 24-month: 1 vs. 2, p = 0.014, 1 vs. 2, p = 0.006), and more mean days to the first readmission (12-month: 270 vs. 209, p = 0.007, 269 vs. 207, p = 0.003; 24-month: 462 vs. 335, p = 0.039, 461 vs. 323, p = 0.005). They also interacted with treatment and alcohol drinking history to predict the outcome. In sex-specific analyses, most of these effects remained significant in males but not in females. Handedness alone did not significantly predict outcome. Moreover, the laterality markers did not significantly differ between alcohol-dependent patients and control subjects. Conclusions: Determining crossed eye/hand laterality and eyedness may help to individualize relapse prevention in the future. Both are easily accessible predictors of alcohol-related readmission following inpatient withdrawal treatment.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Alcohol Dependence; Crossed Eye/Hand Laterality; Eyedness; Relapse Prediction

Cross-national gender variations of digit ratio (2D:4D) correlate with life expectancy, suicide rate, and other causes of death - Lenz, Bernd; Kornhuber, Johannes (Journal of Neural Transmission, 2018)
The second-to-fourth finger length ratio (2D:4D) is an indication of prenatal sex hormone exposure, and has sex-specifically been associated with several lethal illnesses including ischemic heart disease, diverse cancers, and suicide. Our primary aim was to verify that 2D:4D sex-specifically relates to life expectancy and suicide numbers on a national level (23 countries). We also used a hypothesis-free approach to investigate associations with other causes of death [p value adjustment for multiple hypothesis testing using the false discovery rate procedure (FDR)]. All parameters were normalized to the national mean (of males and females) and analyzed across nations. Normalized male 2D:4D correlated positively with normalized male life expectancy (at birth, r = 0.46, p = 0.029; at the age of 60, r = 0.44, p = 0.038) and negatively with normalized male suicide rates (r = - 0.49, p = 0.017). In the exploratory analyses, the normalized male 2D:4D values were negatively associated with the normalized male deaths rates from communicable, maternal, perinatal, and nutritional conditions [r = - 0.65, p(FDR) = 0.011], respiratory infections [r = - 0.69, p(FDR) = 0.008], asthma [r = - 0.65, p(FDR) = 0.011], neurological conditions [r = - 0.56, p(FDR) = 0.046], and Alzheimer's disease and other dementias [r = - 0.59, p(FDR) = 0.036]. The normalized female parameters showed the same cross-national correlations. In line with the previous individual level findings, the results suggest that prenatal sex hormone effects are sex-specifically involved in suicide and neurological conditions. Moreover, we provide novel national level evidence that prenatal sex hormone priming may sex-specifically influence life expectancy and death risk from respiratory diseases.
EVALuna2:35462

Cross-Sectional and Longitudinal Evaluation of the Social Network Use Disorder and Internet Gaming Disorder Criteria - Bouna-Pyrrou, Polyxeni; Aufleger, Birte; Braun, Simona; Gattnar, Manja; Kallmayer, Sofia; Wagner, Helena; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Frontiers in Psychiatry, 2018)
Background: The inclusion of internet gaming disorder (IGD) as a condition warranting more research in the DSM-5 has led to a rapid increase of research on addictive internet activities. Further evaluation of the criteria for IGD and social network disorder (SND) is needed. Objective: To assess the internal consistency, construct validity, retest-reliability, and long-term stability of SND and IGD criteria in German-speaking cohorts. Method: We conducted total and sex-specific analyses on data from two cross-sectional and longitudinal studies, one sample of 192 participants enriched for internet use and another community-based sample of 2316 individuals. Results: First, independent from assessment setting (online, telephone, on-site) and gender, we found acceptable to good internal consistency for SND and IGD criteria (Cronbach's α 0.690-0.774 for SND and 0.743-0.866 for IGD, respectively). Second, positive Spearman correlations between the sum of affirmed criteria and established scales of pathological internet use (ρ 0.395-0.783) and time spent on the social networking sites or internet gaming (ρ 0.317-0.761) confirmed convergent validity. Moreover, the sum of affirmed criteria related positively to attentional impulsivity (ρmax 0.311), urgency (ρ 0.124-0.200), and neuroticism (ρmax 0.210), and negatively to perseverance (ρ -0.245- -0.098) and conscientiousness (ρmin -0.257). Finally, SND and IGD criteria showed high retest stability (SND ρ 0.653-0.826, IGD ρ 0.714-0.825, respectively). However, participants scored higher on SND and IGD scales during the online compared to the on-site assessment. The 2-year follow-up revealed an increase in affirmed SND and IGD criteria. Conclusion: Our data support good psychometric properties of the SND and IGD criteria and outline the addictive potential of social networking sites.
EVALuna2:211611

Die Bedeutung mütterlicher präpartaler Depression und Mutter-Kind-Bindung für die Entwicklung der kindlichen Emotionsregulation: Erste Befunde einer Längsschnittstudie - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Digit ratio (2D:4D) and academic success as measured by achievement in the academic degree "Habilitation" - Tektas, Ozan Yueksel; Kapsner, Lorenz; Lemmer, Miriam; Bouna-Pyrrou, Polyxeni; Lewczuk, Piotr; Lenz, Bernd; Kornhuber, Johannes (PLoS ONE, 2019)
Introduction
CRIS-Team WoS Importer:2019-03-15

Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369

Digit ratio (2D:4D) and transgender identity: new original data and a meta-analysis - Siegmann, Eva-Maria; Müller, Tobias; Dziadeck, Isabelle; Mühle, Christiane; Lenz, Bernd; Kornhuber, Johannes (Scientific Reports, 2020)
Previously reported associations between second-to-fourth digit length ratio (2D:4D), a proxy for prenatal androgen load, and transgender identity have been inconsistent. The objectives of the present study were to provide additional original data and an updated meta-analysis concerning this association. In a study of 464 participants, we compared the 2D:4D of transgender individuals with age- and sex-matched controls. Patients were recruited at a specialized psychiatrist’s medical office, whereas controls were hired via flyers, advertisements, and as convenience sample. A random-effects meta-analysis of the literature (17 samples, n = 3674) also quantifies the overall magnitude of the difference in 2D:4D between transgender individuals and controls. In our study providing new original data, we found a significantly higher (i.e. feminized) left-hand 2D:4D in the male-to-female transgender (MtF) identity [mean age: 32.3 (18; 61)] than in the male control group [mean age: 34.5 (18; 65)] with a Cohen’s d = 0.271. Concordantly, the meta-analytic results suggest a significant difference in 2D:4D among MtF individuals compared to male controls [g = 0.153; 95% CI (0.063; 0.243)], which was even more pronounced when individuals had been diagnosed by a clinician instead of self-identified as transgender [g = 0.193; 95% CI (0.086; 0.300)]. In both studies, no significant results were revealed for female-to-male transgender individuals [mean age: 26.1 (18; 53)] versus female controls [mean age: 27.2 (18; 55)]. This original investigation and the updated meta-analysis clarify the association between transgender identity and 2D:4D indicating the influence of prenatal androgen on the development of gender identity in subjects born as males.
CRIS-Team Scopus Importer:2020-11-20

Digit ratio (2D:4D) in relation to substance and computer use: a meta-analysis - Siegmann, Eva-Maria; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Journal of Neural Transmission, 2019)
Human studies have reported inconsistent associations between the length ratio of the second finger to the fourth finger (2D:4D), which is a proxy for prenatal androgen load, and substance or computer use in adolescents and adults. This meta-analysis quantifies the magnitude of this relationship and investigates the roles of sex, definition of caseness, different forms of addiction, the hand measured (right hand versus left hand), and other cohort characteristics. Univariate random-effects meta-analyses were performed, and moderators were tested with Bonferroni-corrected meta-regression analyses. The study included 18 independent samples with a total of 175,955 participants (96,316 males and 79,639 females). There was a significant difference in 2D:4D between the substance and computer-using subjects and the controls for the combined sample (Hedge’s g = − 0.178 [− 0.291; − 0.064]) and for males (Hedge’s g = − 0.260 [− 0.399; − 0.122]), but not for females. These effects were amplified when only analyzing studies that compared dependent versus non-dependent subjects (combined sample: g = − 0.325 [− 0.492; − 0.157]; males: g = − 0.427 [− 0.564; − 0.291]), but did not reach significance in the subgroup of studies examining other parameters of substance and computer use. When analyzing different forms of substance and computer use separately, alcohol intake and computer use revealed a significant difference in the standardized mean. Again, the effects were amplified when analyzing the subgroup of males and the subgroup of studies comparing dependent versus non-dependent subjects, with effect sizes showing Hedge’s g values as many as − 0.552 [− 0.785; − 0.319] (alcohol-dependent males). Thus, this meta-analysis confirms that lower 2D:4D is associated with substance and computer dependency. Further studies are encouraged to explore the link between intrauterine hormone environment and addiction risk.
CRIS-Team Scopus Importer:2019-05-14
Keywords: 2D:4D; Alcohol; Androgens; Brain organization; Prenatal androgen exposure; Substance use; Testosterone; Tobacco

Digit Ratio (2D:4D) Is Not Associated with Alzheimer’s Disease in the Elderly - Siegmann, Eva-Maria; Olm, Pauline; Lenz, Bernd; Mühle, Christiane; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes (Brain Sciences, 2023)
The development of Alzheimer’s disease (AD) is influenced by sex hormones—estrogens and androgens in particular. However, the impact of prenatal sex hormone exposure is less clear; very few investigations have examined the relationship between the second-to-fourth digit length ratio (2D:4D), a putative proxy for the ratio of prenatal estrogens to androgens, and AD, with inconsistent results among the few that have. Therefore, we aimed to investigate this relationship using methodologically robust metrics. In a 2 (sex) × 4 (group) MANOVA incorporating 108 participants (30 AD patients, 19 patients with tauopathy but no amyloidopathy, 31 clinical and 28 healthy age- and education-matched controls), the effects of sex and group on the dependent variables right and left 2D:4D were examined. We also explored the association between 2D:4D and the severity of AD symptoms assessed via neuropsychological examination. We did not find any significant differences in the right- and left-hand 2D:4D between patients with AD and the other groups; no significant associations between 2D:4D and neuropsychological task performances were found in the dementia groups. The 2D:4D of healthy women was significantly lower than that of depressed women without AD, i.e., clinical controls, but not significantly different from depressed female patients with AD. This investigation does not support the role of 2D:4D in the development or severity of AD in general, but suggests a potential role of 2D:4D for depression in women. Future studies are warranted to clarify whether 2D:4D can distinguish between early- and late-onset depression in women.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Alzheimer’s disease; dementia; digit ratio; fetal development; finger length ratio

DNA methylation of the LEP gene is associated with craving during alcohol withdrawal - Hillemacher, Thomas; Weinland, Christian; Lenz, Bernd; Kraus, Thomas; Heberlein, Annemarie; Glahn, Alexander; Muschler, Marc A. N.; Bleich, Stefan; Kornhuber, Johannes; Frieling, Helge (Psychoneuroendocrinology, 2015)
Different studies have described evidence for an association between leptin serum levels and craving in alcohol dependent patients. As leptin expression is regulated by DNA methylation we investigated changes of DNA methylation of the LEP gene promoter region in alcohol dependent patients undergoing withdrawal. Results show that low methylation status is associated with increasing serum leptin levels and elevation of craving for alcohol in the referring patients group. These findings point towards a pathophysiological relevance of changes in DNA methylation of the LEP gene promoter region in alcohol dependence.
EVALuna2:23715

Effect of a Multi-Dimensional and Inter-Sectoral Intervention on the Adherence of Psychiatric Patients - Pauly, Anne; Wolf, Carolin; Mayr, Andreas; Lenz, Bernd; Kornhuber, Johannes; Friedland, Kristina (PLoS ONE, 2015)
In psychiatry, hospital stays and transitions to the ambulatory sector are susceptible to major changes in drug therapy that lead to complex medication regimens and common non-adherence among psychiatric patients. A multi-dimensional and inter-sectoral intervention is hypothesized to improve the adherence of psychiatric patients to their pharmacotherapy.269 patients from a German university hospital were included in a prospective, open, clinical trial with consecutive control and intervention groups. Control patients (09/2012-03/2013) received usual care, whereas intervention patients (05/2013-12/2013) underwent a program to enhance adherence during their stay and up to three months after discharge. The program consisted of therapy simplification and individualized patient education (multi-dimensional component) during the stay and at discharge, as well as subsequent phone calls after discharge (inter-sectoral component). Adherence was measured by the "Medication Adherence Report Scale" (MARS) and the "Drug Attitude Inventory" (DAI).The improvement in the MARS score between admission and three months after discharge was 1.33 points (95% CI: 0.73-1.93) higher in the intervention group compared to controls. In addition, the DAI score improved 1.93 points (95% CI: 1.15-2.72) more for intervention patients.These two findings indicate significantly higher medication adherence following the investigated multi-dimensional and inter-sectoral program.German Clinical Trials Register DRKS00006358.
EVALuna2:5516

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of prenatal alcohol exposition on cognitive outcomes in childhood and youth: a longitudinal analysis based on meconium ethyl glucuronide. - Roetner, Jakob; Van Doren, Jessica; Maschke, Janina; Kulke, Louisa; Pontones, Constanza; Fasching, Peter A.; Beckmann, Matthias W.; Lenz, Bernd; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (European archives of psychiatry and clinical neuroscience, 2024)
BACKGROUND: Prenatal alcohol exposure (PAE) has been linked to severe, adverse child outcomes. However, little is known regarding subclinical outcomes of low/moderate PAE and its longitudinal consequences, especially regarding neurophysiological and neurocognitive development. A newborn biomarker of PAE, meconium ethyl glucuronide (EtG), has been shown to predict cognitive impairments in primary-school-aged children. The current study investigated the ongoing effects of subclinical PAE in adolescence. METHODS: A sample of n = 96 mother-child dyads of the FRAMES/FRANCES cohort were classified into PAE/no PAE using EtG with a 10 ng/g cutoff. Mothers were recruited during pregnancy and children were assessed during primary-school age (M = 7.57, SD = 0.65, range: 6.00-9.92 years) and adolescence (M = 13.26, SD = 0.31, range: 12.79-14.20 years) on three levels: clinical (ADHD rating), neuropsychological (IQ score and performance in a go/nogo task), and neurophysiological (analysis of P3 event-related potentials (ERP) during said go/nogo task). Developmental outcomes and courses following PAE were assessed using rmANCOVAs, controlling for relevant confounders (socioeconomic status (SES), birth weight, and maternal psychopathology). RESULTS: Neurophysiological impairments emerged for exposed children in the form of diminished attentional resource recruiting in childhood and adolescence (reduced go-P3 amplitudes) with no differences in performance. Neuropsychological testing showed a reduced IQ score for both time points with dose-dependent effects in childhood. Clinical ADHD symptoms were not significantly affected. CONCLUSION: Subclinical PAE, as determined by meconium EtG, has negative developmental consequences on cognitive function that persist from childhood to adolescence. These findings suggest that there is no safe limit for alcohol consumption during pregnancy and that more thorough screening of alcohol consumption during pregnancy is necessary for early identification and treatment of at-risk children.
EVALuna2:538816

Elevated Oxytocin Receptor Blood Concentrations Predict Higher Risk for, More, and Earlier 24-Month Hospital Readmissions after In-Patient Detoxification in Males with Alcohol Use Disorder - Mühle, Christiane; Mazza, Massimiliano; Weinland, Christian; von Zimmermann, Claudia; Bach, Patrick; Kiefer, Falk; Grinevich, Valery; Zoicas, Iulia; Kornhuber, Johannes; Lenz, Bernd (International Journal of Molecular Sciences, 2022)
Alcohol use disorder (AUD) is a major global mental health challenge. Knowledge concerning mechanisms underlying AUD and predictive biomarkers of AUD progression and relapse are insufficient. Recently, addiction research is focusing attention on the oxytocin system. However, to our knowledge, blood concentrations of the oxytocin receptor (OXTR) have not yet been studied in AUD. Here, in sex-separated analyses, OXTR serum concentrations were compared between early-abstinent in-patients with AUD (113 men, 87 women) and age-matched healthy controls (133 men, 107 women). The OXTR concentrations were correlated with sex hormone and oxytocin concentrations and alcohol-related hospital readmissions during a 24-month follow-up. In male patients with AUD, higher OXTR concentrations were found in those with an alcohol-related readmission than in those without (143%; p = 0.004), and they correlated with more prospective readmissions (rho = 0.249; p = 0.008) and fewer days to the first readmission (rho = -0.268; p = 0.004). In men and women, OXTR concentrations did not significantly differ between patients with AUD and controls. We found lower OXTR concentrations in smokers versus non-smokers in female patients (61%; p = 0.001) and controls (51%; p = 0.003). In controls, OXTR concentrations correlated with dihydrotestosterone (men, rho = 0.189; p = 0.030) and testosterone concentrations (women, rho = 0.281; p = 0.003). This clinical study provides novel insight into the role of serum OXTR levels in AUD. Future studies are encouraged to add to the available knowledge and investigate clinical implications of OXTR blood concentrations.
CRIS-Team WoS Importer:2022-09-23

Estrogen receptor 1 gene variants and estradiol activities in alcohol dependence - Mühle, Christiane; Barry, Brianna; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2019)
Objective: Alcohol use disorders inflict a great individual and societal burden. Although sex hormone effects have been implicated in alcohol dependence, research has mostly neglected estrogen activities and female alcohol- dependent patients. Here, we investigated associations of estrogen receptor 1 (ESR1) genetics and serum estradiol activities with aspects of alcohol dependence.
CRIS-Team WoS Importer:2019-05-24

Evaluation of the German biographic screening interview for fetal alcohol spectrum disorder (BSI-FASD) - Widder, Michael; Mierzwa, Luisa; Schwerg, Lina; Schecke, Henrike; Kornhuber, Johannes; Bouna-Pyrrou, Polyxeni; Bumb, Jan Malte; Richter-Schmidinger, Tanja; Lenz, Bernd (Scientific Reports, 2021)
Alcohol consumption during pregnancy may lead to permanent damage in the offspring, including fetal alcohol spectrum disorders (FASD), which have an estimated prevalence of 1–8% worldwide. In adulthood, diagnosing FASD is time-consuming and costly. This study aimed to evaluate the discriminatory power of a German screening instrument for FASD in adults—the biographic screening interview (BSI-FASD). In an open-label comparative cohort study wherein a one-time survey was administered per participant, we compared 22 subjects with confirmed FASD with control groups of 15 subjects diagnosed with attention deficit hyperactivity disorder (ADHD), 20 subjects with alcohol or opiate dependence, 18 subjects with depression, and 31 controls without prenatal alcohol exposure. The BSI-FASD was found to be resource-efficient, user-friendly, comprehensible, and easily applicable. It provided an overall good convergent and discriminant validity with a sensitivity of 0.77 (adapted 0.86) and specificities between 0.70 and 1.00. The BSI-FASD subdomains differed in their power to differentiate FASD from the groups. This study established that the BSI-FASD is an efficient instrument to screen adults with suspected FASD. The BSI-FASD may facilitate future diagnostic evaluation and thereby contribute to improved treatment of affected individuals.
CRIS-Team Scopus Importer:2021-03-19

Ex vivo glucocorticoid receptor-mediated IL-10 response predicts the course of depression severity - von Zimmermann, Claudia; Böhm, Lea; Richter-Schmidinger, Tanja; Kornhuber, Johannes; Lenz, Bernd; Mühle, Christiane (Journal of Neural Transmission, 2021)
Directly measuring hypothalamic pituitary adrenal (HPA) axis function, an important player in affective disorders, is intensive and invasive. A crucial component of this system, the activity of the glucocorticoid receptor (GR), can be assessed ex vivo instead. Here, we investigated GR sensitivity in patients with major depressive disorder (MDD) to determine its predictive potential. Psychometric data and blood samples were collected from patients experiencing a major depressive episode (MDE, n = 87), healthy control subjects (n = 49), and patients with remitted MDD (n = 31) at baseline and (for patients) after median 20 days of follow-up after treatment as usual. Blood cells were stimulated ex vivo with lipopolysaccharide and the effect was suppressed by increasing dexamethasone (DEX) concentrations. The resultant cytokine secretion profile (for IL-6, IL-10, and TNF-α) was considered indicative of GR activity. Higher baseline scores of the Montgomery–Åsberg Depression Rating Scale (MADRS) were associated with a stronger decrease of logIC IL-6 (indicating an increase of GR sensitivity). Higher baseline logEC IL-10 (indicating a lower GR sensitivity) and a stronger reduction of logEC IL-10 (indicating a stronger increase in GR sensitivity) were associated with a stronger decrease in the MADRS score. Patients with remitted MDD showed higher logIC TNF-α values (indicating lower GR sensitivity) in comparison to patients with a current MDD at baseline and follow-up. Initially low GR sensitivity measured ex vivo in peripheral blood cells that increases over the course of treatment could serve as a predictive marker for stronger improvement in depression severity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cytokines; Depression; Glucocorticoid receptor; Hypothalamic–pituitary–adrenal axis

Gaming and Religion: The Impact of Spirituality and Denomination - Braun, Birgit; Kornhuber, Johannes; Lenz, Bernd (Journal of Religion & Health, 2016)
A previous investigation from Korea indicated that religion might modulate gaming behavior (Kim and Kim in J Korean Acad Nurs 40:378-388, 2010). Our present study aimed to investigate whether a belief in God, practicing religious behavior and religious denomination affected gaming behavior. Data were derived from a Western cohort of young men (Cohort Study on Substance Use Risk Factors, n = 5990). The results showed that a stronger belief in God was associated with lower gaming frequency and smaller game addiction scale scores. In addition, practicing religiosity was related to less frequent online and offline gaming. Finally, Christians gamed less frequently and had lower game addiction scale scores than subjects without religious denomination. In the future, these results could prove useful in developing preventive and therapeutic strategies for the Internet gaming disorder.
EVALuna:34140

Internet gaming disorder, social network disorder and laterality: handedness relates to pathological use of social networks - Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Journal of Neural Transmission, 2015)
The internet age bears new challenges that include health risks. It is agreed that excessive internet use may reach pathological levels. However, the concept of internet addiction lacks specificity and, therefore, warrants studies on its diagnostic and etiologic classification. This study was conducted to characterize the novel DSM-5 criteria for internet gaming disorder and the adapted criteria for the "social network disorder". Based on the established association of handedness and substance use disorders, we also explored whether internet use related to laterality. For this study, 3,287 volunteers participated in the online survey and gave particulars concerning their internet use in general, internet gaming and use of social networks, laterality markers (hand, foot, eye, ear, rotational preference in gymnastics, and head turning asymmetry) and health status. Of the participants, 1.1 % fulfilled the criteria for internet gaming disorder, and 1.8 % fulfilled the criteria for social network disorder. The applied criteria were highly correlated with the time spent on the respective internet activities (p < 4 × 10(-56)). The analyses of comorbidity and working hours support the thresholds of 5/9 criteria and >=30 h/week spent on the internet for the classification as pathological (p < 5 × 10(-2)). Moreover, we found that left-handedness related to more affirmed criteria and longer times spent on social networks (p <= 4 × 10(-2)). The provided criteria proved to be user-friendly, comprehensible and well accepted. The results contribute to a better understanding of pathological internet gaming and social network use and provide evidence that biological markers of substance use disorders are involved in internet addiction.
EVALuna2:23695

Korrelate der Depressivität von Müttern von Grundschulkindern - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

LDL cholesterol relates to depression, its severity, and the prospective course - Wagner, Claudia; Musenbichler, Cornelia; Böhm, Lea; Färber, Katharina; Fischer, Anna-Isabell; von Nippold, Felicitas; Winkelmann, Merle; Richter-Schmidinger, Tanja; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2019)
Background: Major depressive disorder (MDD) is a highly prevalent and burdening mental illness. Approximately 30% of the major depressive episodes (MDE) are classified as therapy-refractory. Further knowledge of the pathophysiological mechanisms underlying MDD and predictive biomarkers are needed to improve treatment options. Methods: Serum lipid levels were compared between patients with a current MDE (n = 130) or remitted MDD (n = 39) and healthy control subjects (n = 61) and associated with the severity (17-item Hamilton Depression Rating Scale [HAMD] scores) and the prospective course of depression (direct follow-up of at median 20 days post-inclusion). Results: We found higher levels of LDL cholesterol (152.5 vs. 134.0 mg/dl, U = 3021, P = 0.008) and LDL/HDL ratio (2.82 vs. 2.21, U = 2912, P = 0.003) in patients with a current MDE than in healthy control subjects. In patients with a current MDE, higher HAMD scores correlated also with higher values of triglycerides (ρ = 0.213, P = 0.015), total cholesterol (ρ = 0.199, P = 0.023), LDL cholesterol (ρ = 0.224, P = 0.010), and LDL/HDL ratio (ρ = 0.196, P = 0.026). Moreover, higher total cholesterol (ρ = −0.233, P = 0.010), LDL cholesterol (ρ = 0.235, P = 0.010), and LDL/HDL ratio (ρ = −0.199, P = 0.029) were associated with a stronger decline in HAMD score between study inclusion and direct follow-up. Limitations: We employed an associational study design, performed only a short-term follow-up, and excluded suicidal study subjects. Conclusions: Serum lipid levels are associated with depression per se, the depression severity, and the prospective 3-week course. These observations build the basis for future investigations on individualized lipid metabolism-related treatment strategies in depressed patients.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cholesterol; Depression; LDL cholesterol; Serum lipids; Triglycerides

Low digit ratio (2D:4D) and late pubertal onset indicate prenatal hyperandrogenziation in alcohol binge drinking - Lenz, Bernd; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Kornhuber, Johannes (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2018)
BACKGROUND: Alcohol binge drinking behavior is an important public health issue. Causal rodent and human associational studies show that reinforcement of prenatal androgen signaling increases alcohol consumption in adulthood. However, the effects of prenatal androgen exposure on adult binge drinking patterns have not been investigated yet. METHOD: We analyzed data from 2225 participants of an online survey (conducted 06-07/2016) to evaluate biomarkers for prenatal androgen exposure (second-to-fourth finger length ratio [2D:4D], age at spermarche or menarche as hallmark for pubertal onset) in binge drinking (≥1 episode of 15+, 10+, and/or 5+ standard drinks of 13 g of alcohol within 2 h during the 24 month- and 2 week-recall periods). RESULTS: Men reported binge drinking more often than women (ORs > 1.4, P < .001). For the 24 month-recall period, binge drinkers showed lower 2D:4D (P = .006) and reported later pubertal onset (P = .022) than non-binge drinkers. These findings consistently suggest excess prenatal androgen exposure in adult binge drinkers. Moreover, 2D:4D was negatively associated with severity (15+/10+/5+/non-binge drinking, P = .005) and frequency of binge drinking episodes (P = .044). All of these effects were stronger in men than in women. For the 2 week-recall period, the biomarkers were not significantly related to binge drinking behavior. CONCLUSION: Our results indicate that increased prenatal androgen exposure is involved in the development of alcohol binge drinking behavior in adults.
EVALuna2:211636

Low digit ratio (2D:4D) in male suicide victims - Lenz, Bernd; Thiem, Daniela; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Stoessel, Christina; Betz, Peter; Kornhuber, Johannes (Journal of Neural Transmission, 2016)
Although women attempt suicides equally or more often than men do, men are more likely to die of suicide than women (sex paradox of suicidal behavior). Furthermore, the male traits of aggression and impulsivity predict suicide completion. Here, we studied the second-to-fourth-finger length ratio (2D:4D), a proxy for prenatal androgen exposure, in 46 suicide corpses and 25 non-suicide corpses. We report significantly lower 2D:4D in male suicide corpses than non-suicide corpses (p = .030, partial ? (2) = .147). There was no significant association between 2D:4D and the suicide method. Our findings indicate increased risk of suicide following higher prenatal androgen exposure in males. The results may improve future efforts to predict and prevent suicides.
EVALuna2:9427

Lower digit ratio (2D:4D) in alcohol dependence: Confirmation and exploratory analysis in a population-based study of young men - Lenz, Bernd; Mühle, Christiane; Kornhuber, Johannes (Addiction Biology, 2019)
Moderately sized, case-control studies have related alcohol dependence in middle-aged in-patients to lower second-to-fourth finger length ratio (2D:4D), a proxy for prenatal hyperandrogenization. As primary aim, we here intended to confirm that lower 2D:4D is also associated with Diagnostic and Statistical Manual of Mental Disorders (DSM)–IV/-5 alcohol dependence and alcohol use disorder in a large population-based cohort of young males. Exploratory aims included underlying mechanisms. We analyzed self-reported data on 2D:4D, DSM-IV/-5 criteria, anticipated subjective responses to alcohol, and willingness to purchase alcoholic drinks from 4989 Swiss men of the Cohort Study on Substance Use Risk Factors (C-SURF). The mean of right-hand 2D:4D and left-hand 2D:4D was lower in men with DSM-IV alcohol dependence than in those without (0.975 vs 0.981, P =.035) and lower in men with moderate to severe (0.974) than in those with mild (0.982, P =.001) or no (0.981, P =.003) DSM-5 alcohol use disorder. Moreover, mean 2D:4D was lower in those reporting recent use of health services due to substance use problems (0.968 vs 0.981, P =.046). Lower mean 2D:4D correlated with a stronger anticipation to feel high following alcohol consumption (total cohort: ρ = −0.033, P =.026) and with a willingness to purchase more higher-priced alcoholic drinks (DSM-IV alcohol dependence subgroup: ρmin = −0.162, P =.002). This is the first population-based study on young males to demonstrate lower 2D:4D in DSM-IV alcohol dependence, DSM-5 alcohol use disorder, and the related use of health care services. We also provide novel insight into cognitive-behavioral mechanisms. These results should help to establish more effective preventive and therapeutic strategies targeting 2D:4D and prenatal androgen exposure.
CRIS-Team Scopus Importer:2019-08-27
Keywords: 2D:4D; alcohol dependence; alcohol use disorder; digit ratio

Lower Digit Ratio (2D:4D) Indicative of Excess Prenatal Androgen Is Associated With Increased Sociability and Greater Social Capital - Buchholz, Verena N.; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd; Gmel, Gerhard; Mohler-Kuo, Meichun; Foster, Simon; Marmet, Simon; Studer, Joseph (Frontiers in Behavioral Neuroscience, 2019)
Positive social interactions are crucial for human well-being. Elevated prenatal exposure to testosterone as indicated by a low second-to-fourth finger length ratio (2D:4D) relates to more aggressive/hostile behavior in men of low 2D:4D, especially in challenging situations. How much people enjoy interacting with others is determined by the personality trait sociability. Given its role in approach and avoidance behavior, sociability might also be influenced by prenatal sex hormones, but studies are inconclusive so far. Here, we investigated the association between 2D:4D and the personality trait sociability complemented by personal social capital and personal social network size, in a population-based cohort of 4998 men. Lower 2D:4D correlated significantly with higher trait sociability, bigger personal social capital, and larger personal social network size. These effects were consistent across both hands separately and their mean value. Furthermore, both factors of sociability (1) liking party and company of friends and (2) isolation intolerance, correlated significantly with the prenatal testosterone marker. The exploratory analysis revealed no link between 2D:4D and responses to the personality trait aggression items or items of anti-social-personality disorder. Our data suggest that prenatal androgen exposure organizes the brain with lasting effects on social behavior.
CRIS-Team WoS Importer:2020-01-03

Macrophage Migration Inhibitory Factor in Major Depressive Disorder: A Multilevel Pilot Study - Swoboda, Caroline; Deloch, Lena; von Zimmermann, Claudia; Richter-Schmidinger, Tanja; Lenz, Bernd; Kornhuber, Johannes; Mühle, Christiane (International Journal of Molecular Sciences, 2022)
Macrophage migration inhibitory factor (MIF) is a controversially discussed inflammatory marker in major depressive disorder (MDD). While some studies show an association of high MIF protein levels with depression, animal models have yielded conflicting results. Thus, it remains elusive as to whether MIF plays an anti- or pro-depressive role. Therefore, we aimed to examine the potential of MIF at the genetic, expression and protein levels as a risk factor and biomarker to diagnose, monitor, or predict the course of MDD. Patients with a current major depressive episode (n = 66 with, and n = 63 without, prior medication) and remitted patients (n = 39) were compared with healthy controls (n = 61). Currently depressed patients provided a second blood sample after three weeks of therapy. Depression severity was assessed by self-evaluation and clinician rating scales. We genotyped for three MIF polymorphisms and analyzed peripheral MIF expression and serum levels. The absence of minor allele homozygous individuals in the large group of 96 female patients compared with 10-16% in female controls suggests a protective effect for MDD, which was not observed in the male group. There were no significant group differences of protein and expression levels, however, both showed predictive potential for the course of depression severity in some subgroups. While MIF protein levels, but not MIF expression, decreased during treatment, they were not associated with changes in depression severity. This project is the first to investigate three biological levels of MIF in depression. The data hint toward a genetic effect in women, but do not provide robust evidence for the utility of MIF as a biomarker for the diagnosis or monitoring of MDD. The observed predictive potential requires further analysis, emphasizing future attention to confounding factors such as sex and premedication.
CRIS-Team WoS Importer:2023-01-20
Keywords: major depressive disorder; macrophage migration inhibitory factor (MIF); biomarker; inflammation

Male depression syndrome is characterized by pronounced Cluster B personality traits - Sedlinská, Terezie; Mühle, Christiane; Richter-Schmidinger, Tanja; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of Affective Disorders, 2021)
Background: Male depression syndrome (Male-DS) refers to alternative depression symptoms related to the male sex, such as externalizing behaviors, emotional suppression, substance misuse, and risk-seeking. Although these symptoms contribute to gender bias in the diagnosis of depression, Male-DS can be found in both sexes. In this cross-sectional study, we analyzed associations between Male-DS and clinical personality accentuations. Methods: We compared clinical personality accentuations between 78 depressed patients with high Male-DS scores (46% women; mean age ± standard error of the mean: 36.5 ± 1.6 years) and 76 depressed patients with low Male-DS scores (43% women; age 44.8 ± 1.7 years). We also explored differences between the two patient groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years). Results: Depressed patients with high Male-DS scores showed stronger borderline (partial η2 0.121), impulsive (0.112), and antisocial (0.078) personality accentuations than those with low Male-DS scores after Bonferroni adjustment and controlling for sex, depression severity, and age. Relative to healthy controls, patients with high Male-DS values scored higher in all personality dimensions except for the narcissistic dimension. Patients with low Male-DS values scored higher in all Cluster A and C dimensions and the impulsive and borderline dimensions, but their scores were lower in the narcissistic dimension. Limitations: Cross-sectional design and focus on in-patients. Conclusions: We found pronounced Cluster B personality in patients with high Male-DS scores versus patients with low scores. Further prospective research is needed to verify that Cluster B personality traits represent a pre-morbid risk factor for Male-DS.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Antisocial; Borderline; Impulsive; Male depression; Personality

Markers of Prenatal Androgen Exposure Correlate With Online Sexual Compulsivity and Erectile Function in Young Men - Buchholz, Verena N.; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2021)
Pornography addiction and sexual dysfunction are increasingly prevalent in young men. Previous studies suggest that prenatal androgen exposure plays a role in addiction and sexual functionality. Here, we tested whether lower second-to-fourth finger length ratio (2D:4D) and later age at spermarche, both putative indicators of higher androgen levels in utero, correlate with online sexual compulsivity (OSC scale of ISST), erectile function (IIEF-5), and ejaculatory control (PEPA) in 4,370 young men (age IQR: 25-26 years) of the Cohort Study on Substance Use Risk Factors. Statistical analyses revealed that lower 2D:4D correlated with higher scores on the OSC scale. Moreover, higher age at spermarche correlated with higher OSC scores and decreased erectile function. Interestingly, OSC severity, but not the frequency of pornography use, correlated negatively with erectile function and ejaculatory control. This is the first study to associate two independent proxies of prenatal testosterone level with OSC. These findings provide novel insight into intrauterine predisposition of sexual behavior and related sexual function in adulthood.
CRIS-Team WoS Importer:2021-05-07

Masculine depression and its problem behaviors: use alcohol and drugs, work hard, and avoid psychiatry! - von Zimmermann, Claudia; Hübner, Magdalena; Mühle, Christiane; Müller, Christian P.; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (European archives of psychiatry and clinical neuroscience, 2023)
The gender role influences vulnerability to mental illness. Substance use, even critical in scale, is perceived as masculine, just like hard (over-)work, while not seeking help. With the ongoing separation between gender and sex, masculine norms become more relevant also to females’ mental health. The male depression concept highlights the role of male symptoms in affective disorders. However, the empirical evidence is still limited. Here, we use the denomination ‘masculine depression’ to open the category for female patients and tested substance use patterns, health services’ utilization, and working hours as predictors in a case–control study of 163 depressed in-patients (44% women; masculine vs. non-masculine depression according to a median split of the Male Depression Rating Scale-22) and 176 controls (51% women). We assessed higher depression severity in patients with masculine (vs. non-masculine) depression. Masculine depression (vs. non-masculine depression and vs. no depression) was predicted by more frequent and critical use of alcohol (including binge drinking), tobacco, and illicit drugs, and by longer working times. Moreover, fewer health services contacts due to mental complaints during the previous year were associated with masculine (vs. non-masculine) depression. Alarmingly, even critical substance misuse was not significantly associated with more frequent health services contacts; however, the higher the depression severity, the more contacts the patients reported. Here, we provide evidence that patients with masculine depression are highly burdened and undertreated, which applies equally to female and male patients. This study identified promising targets to establish specialized care offers.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcoholism; Drug use; Help seeking; Male depression; Masculine depression; Nicotine; Substance use

Maternal perinatal or current depressive symptoms and parenting behavior in middle childhood - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias; Heinrich, Hartmut; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programme's effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
EVALuna2:36366

mRNA expression of SMPD1 encoding acid sphingomyelinase decreases upon antidepressant treatment - Rhein, Cosima; Zoicas, Iulia; Marx, Lena M.; Zeitler, Stefanie; Hepp, Tobias; von Zimmermann, Claudia; Mühle, Christiane; Richter-Schmidinger, Tanja; Lenz, Bernd; Erim, Yesim; Reichel, Martin; Gulbins, Erich; et al. (International Journal of Molecular Sciences, 2021)
Major depressive disorder (MDD) is a severe psychiatric condition with key symptoms of low mood and lack of motivation, joy, and pleasure. Recently, the acid sphingomyelinase (ASM)/ceramide system has been implicated in the pathogenesis of MDD. ASM is a lysosomal glycoprotein that catalyzes the hydrolysis of sphingomyelin, an abundant component of membranes, into the bioactive sphingolipid ceramide, which impacts signaling pathways. ASM activity is inhibited by several common antidepressant drugs. Human and murine studies have confirmed that increased ASM activity and ceramide levels are correlated with MDD. To define a molecular marker for treatment monitoring, we investigated the mRNA expression of SMPD1, which encodes ASM, in primary cell culture models, a mouse study, and a human study with untreated MDD patients before and after antidepressive treatment. Our cell culture study showed that a common antidepressant inhibited ASM activity at the enzymatic level and also at the transcriptional level. In a genetically modified mouse line with depressive-like behavior, Smpd1 mRNA expression in dorsal hippocampal tissue was significantly decreased after treatment with a common antidepressant. The large human study showed that SMPD1 mRNA expression in untreated MDD patients decreased significantly after antidepressive treatment. This translational study shows that SMPD1 mRNA expression could serve as a molecular marker for treatment and adherence monitoring of MDD.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Acid sphingomyelinase; Amitripty-line; Antidepressants; Biomarker; FIASMA; Fluoxetine; Major depressive disorder; SMPD1

Nasales Esketamin zusätzlich zu oralen Antidepressiva: Hilfe bei therapieresistenter Depression? - Lenz, Bernd (Fortschritte der Neurologie - Psychiatrie, 2019)
CRIS-Team Scopus Importer:2019-12-10

Neutral Sphingomyelinase is an Affective Valence-Dependent Regulator of Learning and Memory - Kalinichenko, Liubov; Abdel-Hafiz, Laila; Wang, An Li; Mühle, Christiane; Rösel, Nadine; Schumacher, Fabian; Kleuser, Burkhard; Smaga, Irena; Frankowska, Malgorzata; Filip, Malgorzata; Schaller, Gerd; Richter-Schmidinger, Tanja; et al. (Cerebral Cortex, 2021)
Sphingolipids and enzymes of the sphingolipid rheostat determine synaptic appearance and signaling in the brain, but sphingolipid contribution to normal behavioral plasticity is little understood. Here we asked how the sphingolipid rheostat contributes to learning and memory of various dimensions. We investigated the role of these lipids in the mechanisms of two different types of memory, such as appetitively and aversively motivated memory, which are considered to be mediated by different neural mechanisms. We found an association between superior performance in short- A nd long-term appetitively motivated learning and regionally enhanced neutral sphingomyelinase (NSM) activity. An opposite interaction was observed in an aversively motivated task. A valence-dissociating role of NSM in learning was confirmed in mice with genetically reduced NSM activity. This role may be mediated by the NSM control of N-methyl-d-aspartate receptor subunit expression. In a translational approach, we confirmed a positive association of serum NSM activity with long-term appetitively motivated memory in nonhuman primates and in healthy humans. Altogether, these data suggest a new sphingolipid mechanism of de-novo learning and memory, which is based on NSM activity.
CRIS-Team Scopus Importer:2021-02-12
Keywords: ceramide; learning; memory; neutral sphingomyelinase; sphingomyelin

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

OPRM1 A118G and serum β-endorphin interact with sex and digit ratio (2D:4D) to influence risk and course of alcohol dependence - Gegenhuber, Bruno; Weinland, Christian; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (European Neuropsychopharmacology, 2018)
Activation of mesolimbic mu-opioid receptors by their endogenous ligand, β-endorphin, can mediate the rewarding effects of alcohol. However, there is conflicting evidence on the relationship between the mu-opioid receptor (OPRM1) A118G single nucleotide polymorphism (SNP) and alcohol dependence risk. Preclinical evidence suggests that sex and sex hormone-dependent prenatal brain organization may interact with the opioid system to influence alcohol drinking behavior. We genotyped 200 alcohol-dependent patients and 240 healthy individuals for the OPRM1 A118G SNP and measured serum β-endorphin level at recruitment and after acute withdrawal. We then determined the association between these factors and alcohol dependence risk and 24-month outcome in the context of both sex and second-to-fourth digit lengths ratio (2D:4D) - a biomarker of prenatal sex hormone levels. The OPRM1 A118G AA genotype associated with elevated risk of alcohol-related hospital readmission, more readmissions, and fewer days until first readmission in male patients only. After normalizing patient 2D:4D against control 2D:4D, we found that normalized 2D:4D ratios were lower in male 118G patients than male AA patients, suggesting prenatal androgens interact with OPRM1 to influence alcohol dependence risk. In addition, β-endorphin levels after acute withdrawal correlated negatively with withdrawal severity in females but not in males, which may indicate β-endorphin protects against withdrawal-induced stress in a sex-specific manner.
EVALuna2:211619

Oxytocin blood concentrations in alcohol use disorder: A cross-sectional, longitudinal, and sex-separated study - Lenz, Bernd; Weinland, Christian; Bach, Patrick; Kiefer, Falk; Grinevich, Valery; Zoicas, Iulia; Kornhuber, Johannes; Mühle, Christiane (European Neuropsychopharmacology, 2021)
Alcohol use disorder (AUD) is a severe illness, for which we lack sufficient mechanistic understanding. Preliminary evidence associates AUD with the oxytocin (OXT) system. Here we investigated alterations in endogenous OXT blood concentrations in patients with AUD and their association with alcohol drinking and prospective course. In sex-separated analyses, OXT serum concentrations of 200 in-patients with AUD (56.5% male; baseline, 24–72 h of abstinence) were compared with those of 240 age-matched healthy controls (55.4% male), investigated longitudinally (follow-up, 5 days later), and tested for associations with alcohol drinking behavior and prospective 24-month alcohol-related hospital readmissions. At baseline, the patients showed increased OXT concentrations relative to controls (men, 156%, P < 0.001; women, 124%, P = 0.002). The elevations normalized at follow-up. In male patients, baseline OXT concentrations correlated positively with alcohol concentration at admission, the amount of alcohol consumption per drinking year, and the number of previous withdrawal treatments (Rho > 0.195, P < 0.044). In beverage type-specific analysis, baseline OXT concentrations correlated with liquor consumption positively in male and negatively in female patients (|Rho| > 0.277, P < 0.017). Higher baseline OXT concentrations predicted more readmissions and fewer days to the first readmission (|Rho| > 0.185, P < 0.050) in male patients. This study provides novel and sex-separated insights into the role of the OXT system in AUD. We identified a mechanism that might underlie the sex-separated choice of beverage type and established that increased OXT concentrations during early abstinence predict a worse outcome in male patients with AUD.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Alcohol dependence; Alcohol use disorder; Alcoholic beverages; Alcoholism; Ethanol; Oxytocin; Patient readmission; Prospective studies

Peripheral Acid Sphingomyelinase Activity Is Associated with Biomarkers and Phenotypes of Alcohol Use and Dependence in Patients and Healthy Controls - Mühle, Christiane; Weinland, Christian; Gulbins, Erich; Lenz, Bernd; Kornhuber, Johannes (International Journal of Molecular Sciences, 2018)
By catalyzing the hydrolysis of sphingomyelin into ceramide, acid sphingomyelinase (ASM) changes the local composition of the plasma membrane with effects on receptor-mediated signaling. Altered enzyme activities have been noted in common human diseases, including alcohol dependence. However, the underlying mechanisms remain largely unresolved. Blood samples were collected from early-abstinent alcohol-dependent in-patients (n[♂] = 113, n[♀] = 87) and matched healthy controls (n[♂] = 133, n[♀] = 107), and analyzed for routine blood parameters and serum ASM activity. We confirmed increased secretory ASM activities in alcohol-dependent patients compared to healthy control subjects, which decreased slightly during detoxification. ASM activity correlated positively with blood alcohol concentration, withdrawal severity, biomarkers of alcohol dependence (liver enzyme activities of gamma-glutamyl transferase, alanine aminotransferase, aspartate aminotransferase; homocysteine, carbohydrate-deficient transferrin; mean corpuscular volume, and creatine kinase). ASM activity correlated negatively with leukocyte and thrombocyte counts. ASM and gamma-glutamyl transferase were also associated in healthy subjects. Most effects were similar for males and females with different strengths. We describe previously unreported associations between ASM activity and markers of liver damage and myelosuppression. Further research should investigate whether this relationship is causal, or whether these parameters are part of a common pathway in order to gain insights into underlying mechanisms and develop clinical applications.
EVALuna2:211614

Peripheral Upregulation of Parkinson’s Disease-Associated Genes Encoding α-Synuclein, β-Glucocerebrosidase, and Ceramide Glucosyltransferase in Major Depression - Brazdis, Razvan Marius; von Zimmermann, Claudia; Lenz, Bernd; Kornhuber, Johannes; Mühle, Christiane (International Journal of Molecular Sciences, 2024)
Due to the high comorbidity of Parkinson’s disease (PD) with major depressive disorder (MDD) and the involvement of sphingolipids in both conditions, we investigated the peripheral expression levels of three primarily PD-associated genes: α-synuclein (SNCA), lysosomal enzyme β-glucocerebrosidase (GBA1), and UDP-glucose ceramide glucosyltransferase (UGCG) in a sex-balanced MDD cohort. Normalized gene expression was determined by quantitative PCR in patients suffering from MDD (unmedicated n = 63, medicated n = 66) and controls (remitted MDD n = 39, healthy subjects n = 61). We observed that expression levels of SNCA (p = 0.036), GBA1 (p = 0.014), and UGCG (p = 0.0002) were higher in currently depressed patients compared to controls and remitted patients, and expression of GBA1 and UGCG decreased in medicated patients during three weeks of therapy. Additionally, in subgroups, expression was positively correlated with the severity of depression and anxiety. Furthermore, we identified correlations between the gene expression levels and PD-related laboratory parameters. Our findings suggest that SNCA, GBA1, and UGCG analysis could be instrumental in the search for biomarkers of MDD and in understanding the overlapping pathological mechanisms underlying neuro-psychiatric diseases.
CRIS-Team Scopus Importer:2024-04-05
Keywords: affective disorder; anxiety; biomarker; GBA1; gene expression; major depressive disorder; MDD; PD; SNCA; UGCG

Pharmacist-Led Medication Reviews to Identify and Collaboratively Resolve Drug-Related Problems in Psychiatry - A Controlled, Clinical Trial - Wolf, Carolin; Pauly, Anne; Mayr, Andreas; Groemer, Teja; Lenz, Bernd; Kornhuber, Johannes; Friedland, Kristina (PLoS ONE, 2015)
This prospective, controlled trial aimed to assess the effect of pharmacist-led medication reviews on the medication safety of psychiatric inpatients by the resolution of Drug-Related Problems (DRP). Both the therapy appropriateness measured with the Medication Appropriateness Index (MAI) and the number of unsolved DRP per patient were chosen as primary outcome measures.Depending on their time of admission, 269 psychiatric patients that were admitted to a psychiatric university hospital were allocated in control (09/2012-03/2013) or intervention group (05/2013-12/2013). In both groups, DRP were identified by comprehensive medication reviews by clinical pharmacists at admission, during the hospital stay, and at discharge. In the intervention group, recommendations for identified DRP were compiled by the pharmacists and discussed with the therapeutic team. In the control group, recommendations were not provided except for serious or life threatening DRP. As a primary outcome measure, the changes in therapy appropriateness from admission to discharge as well as from admission to three months after discharge (follow-up) assessed with the MAI were compared between both groups. The second primary outcome was the number of unsolved DRP per patient after completing the study protocol. The DRP type, the relevance and the potential of drugs to cause DRP were also evaluated.The intervention led to a reduced MAI score by 1.4 points per patient (95% confidence interval [CI]: 0.8-2.0) at discharge and 1.3 points (95% CI: 0.7-1.9) at follow-up compared with controls. The number of unsolved DRP in the intervention group was 1.8 (95% CI: 1.5-2.1) less than in control.The pharmaceutical medication reviews with interdisciplinary discussion of identified DRP appears to be a worthy strategy to improve medication safety in psychiatry as reflected by less unsolved DRP per patient and an enhanced appropriateness of therapy. The promising results of this trial likely warrant further research that evaluates direct clinical outcomes and health-related costs.Deutsches Register Klinischer Studien (DRKS), DRKS00006358.
EVALuna2:5531

Physical Activity and Body Composition Are Associated With Severity and Risk of Depression, and Serum Lipids - von Zimmermann, Claudia; Winkelmann, Merle; Richter-Schmidinger, Tanja; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2020)
Background: Physical activity and a healthy body composition are said to reduce the risk of major depressive disorder. Nonetheless, deeper insight is needed into which specific forms of physical activity (and their relation to body composition) are effective in improving and preventing depressive symptoms. Methods: We compared different self-reported physical activities of the Global Physical Activity Questionnaire and body composition measures between patients with a current major depressive episode (MDE; N = 130) and healthy control subjects (N = 61). These parameters were also tested for correlations with depression severity and serum lipid levels in patients and controls. Results: Patients with a current MDE reported significantly fewer hours spent on total physical activity, walking or bicycling for travel, and vigorous-intensity activities at leisure than healthy control subjects. More time spent on vigorous-intensity activities at work, less time spent on walking or bicycling for travel, higher body fat mass, and lower body muscle mass correlated significantly with stronger depression severity. Physical activity and body measures correlated significantly with serum lipid levels. Limitations: Self-reports of physical activity, only short-term follow-up of 20 days, cross-sectional study design without examination of causal role of exercise. Conclusions: More time spent on traveling by foot or by bike is especially associated with a lower risk of and milder depression. These results highlight the differential role of physical activity in depression.
CRIS-Team Scopus Importer:2020-06-30
Keywords: body composition; depression; mental health; physical activities and sports; serum lipid concentration

Prenatal alcohol exposure and the facial phenotype in adolescents: A study based on meconium ethyl glucuronide - Maschke, Janina; Roetner, Jakob; Goecke, Tamme; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (Brain Sciences, 2021)
Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 29 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5% EtG112+). The craniofacial shape was measured using FAS Facial Photographic Analysis Software. EtG10+− and EtG112+-affected children exhibited a shorter palpebral fissure length (p = 0.031/p = 0.055). Lip circularity was smaller in EtG112+-affected children (p = 0.026). Maternal self-reports were not associated (p > 0.164). Lip circularity correlated with fluid reasoning (EtG10+ p = 0.031; EtG112+ p = 0.298) and working memory (EtG10+ p = 0.084; EtG112+ p = 0.144). The present study demonstrates visible effects of the facial phenotype in exposed adolescents. Facial malformation was associated with a child’s cognitive performance in the alcohol-exposed group. The EtG biomarker was a better predictor than maternal self-reports.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alcohol; Biomarker; Craniofacial shape; Ethyl glucuronide (EtG); Facial malformations; Inner canthal distance; Intrauterine alcohol exposure; Lip circularity; Meconium; Palpebral fissure length

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

Prenatal androgen receptor activation determines adult alcohol and water drinking in a sex-specific way - Huber, Sabine; Zoicas, Iulia; Reichel, Martin; Mühle, Christiane; Büttner, Christian; Ekici, Arif Bülent; Eulenburg, Volker; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Addiction Biology, 2017)
Alcohol use disorders are major psychiatric disorders. Correlational studies in humans suggested organizational hormonal effects during embryonic development as a risk factor for adult alcohol dependence. Permanent changes can be induced by the activity of sex hormones, like testosterone. Here, we demonstrate a relationship between prenatal androgen receptor (AR)-activation and adult alcohol as well as water drinking in mice in a sex-dependent fashion. Prenatal AR inhibition using the antagonist flutamide decreased adult male alcohol consumption. In contrast, prenatal AR activation by dihydrotestosterone (DHT) led to an increase in adult alcohol consumption in females. These effects were different in adult water drinking, flutamide increased water consumption in females and DHT increased water consumption in males. Prenatal flutamide reduced locomotion and anxiety in adult males but was ineffective in females. We found that prenatal AR activation controls adult levels of monoaminergic modulatory transmitters in the brain and blood hormone levels in a sex-specific way. RNA-Seq analysis confirmed a prenatal AR mediated control of adult expression of alcohol drinking-related genes like Bdnf and Per2. These findings demonstrate that prenatal androgen activity is a risk factor for the establishment of alcohol consumption in adults by its organizational effects.
EVALuna2:4035

Prenatal androgen-receptor activity has organizational morphological effects in mice - Huber, Sabine; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (PLoS ONE, 2017)
Prenatal sex hormones exert organizational effects. It has been suggested that prenatal sex hormones affect adult morphological parameters, such as the finger length. Especially the second-to-fourth finger length (2D:4D) ratio has been implicated to be modified when exposed to higher androgen levels in utero. Here we show in a mouse model that experimental manipulation of the prenatal androgen level, by blocking the androgen receptor with flutamide or activating the androgen receptor with dihydrotestosterone (DHT), leads to changes in the length of the fingers of all paws in males and females. In addition to that, also total paw length and the 2D:4D ratio was affected. In males treated with DHT, the 2D:4D ratio was increased, while flutamide-treatment in females led to a reduced 2D:4D ratio. We also measured other parameters, such as head size, body length and tail length and demonstrate that body morphology is affected by prenatal androgen exposure with more prominent effects in females. Another factor that is thought to be influenced by early androgens is handedness. We tested mice for handedness, but did not find a significant effect of the prenatal treatment. These findings demonstrate that prenatal androgen activity is involved in the development of body morphology and might be a useful marker for prenatal androgen exposure.
EVALuna2:33379

Prenatal testosterone activity determines adult alcohol drinking and morphology in mice - Huber, Sabine; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (2016)
EVALuna2:33260

Progesterone serum levels correlate negatively with craving in female postmenopausal in-patients with alcohol use disorder: A sex- and menopausal status-separated study - Weinland, Christian; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2021)
Objective: Alcohol use disorder (AUD) shows a high prevalence and often takes a severe and chronic course. However, the underlying mechanisms still need to be better understood. There is increasing evidence for a role of sex hormones in AUD and for the importance of sex-separated concepts in addiction research. Nevertheless, only few data give insight into how progesterone is involved in AUD. Method: Serum progesterone levels were measured at baseline (during early abstinence) in 186 in-patients with AUD (19% premenopausal females, 20% postmenopausal females, 61% males) and at median 5 days later. They were compared with those of 233 healthy control subjects (24% premenopausal females, 19% postmenopausal females, 57% males). We quantified craving with the Obsessive Compulsive Drinking Scale (OCDS) and visual analogue scales (VAS). Alcohol-related hospital readmissions within a 24-month period following initial in-patient treatment were recorded. We conducted analyses separately for sex and for menopausal status in female participants. Results: Postmenopausal females with AUD reported higher craving than premenopausal females. In postmenopausal females, higher baseline progesterone levels correlated with lower OCDS total craving and VAS craving, i.e., lower state craving and lower average, maximum, and less frequent craving during withdrawal. In males with AUD, progesterone levels at baseline tended to be higher than in controls and declined to follow-up. Alcohol-related readmissions were not significantly associated with serum progesterone levels. Conclusion: We provide first evidence that progesterone levels correlate with craving in females with AUD.
CRIS-Team Scopus Importer:2021-04-23
Keywords: AUD; Craving; Progesterone; Sex hormones

Psychiatric Adolescent Cohorts: self reported Impulsiveness and Suicidal Behaviour - Lenz, Bernd (Fortschritte der Neurologie - Psychiatrie, 2017)
EVALuna2:33576

Religiosity, Guilt, Altruism and Forgiveness in Alcohol Dependence: Results of a Cross-sectional and Prospective Cohort Study - Braun, Birgit; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Alcohol and Alcoholism, 2018)
Aims: To compare religious denomination, religiosity, guilt, altruism and forgiveness between alcohol-dependent patients and healthy control subjects and to prospectively investigate their relationship to the disorder's 24-month course following in-patient withdrawal treatment. Method: This study in Franconia (a mainly Christian protestant region of southern Germany) applied six questionnaires to evaluate religiosity, guilt, altruism and forgiveness in 166 alcohol-dependent in-patients during withdrawal and compared findings with that of 240 healthy controls. Results: Compared to controls religious denomination was more frequently reported by the patients (OR = 1.72, P = 0.014) and patients showed higher guilt (P < 0.001). The subjective attainability of altruism was lower in patients than in controls (P = 0.015). Higher scores on scale of inter-religious private practice predicted earlier (Rho = -0.184, P = 0.021) and more frequent alcohol-related readmissions during the follow-up (Rho = 0.207, P = 0.009). Higher religious affiliation was related to earlier (Rho = -0.214, P = 0.008) and more frequent alcohol-related readmissions (Rho = 0189, P = 0.020). Lower values of subjective attainability of altruism predicted a worse outcome (earlier [Rho = 0.231, P = 0.003] and more frequent readmissions [Rho = -0.223, P = 0.004]). The sex-specific analyses show that some of the associations are stronger in women and others are stronger in men; however, these gender differences are small and possibly biased by multiple hypothesis testing. Conclusions: We identified religious denomination, private religious practice, religious affiliation, guilt and reduced attainability of altruism as risk factors for alcohol dependence and a worse follow-up outcome. Our findings may help to establish future preventive and therapeutic strategies.
EVALuna2:211631

Secretory Acid Sphingomyelinase in the Serum of Medicated Patients Predicts the Prospective Course of Depression - Mühle, Christiane; Wagner, Claudia; Färber, Katharina; Richter-Schmidinger, Tanja; Gulbins, Erich; Lenz, Bernd; Kornhuber, Johannes (Journal of Clinical Medicine, 2019)
Major depressive disorder (MDD) is a highly prevalent and devastating psychiatric illness with strong individual and societal burdens. However, biomarkers to improve the limited preventive and therapeutic approaches are scarce. Multilevel evidence suggests that the pathophysiological involvement of sphingolipids particularly increases the levels of ceramides and the ceramide hydrolyzing enzyme, acid sphingomyelinase. The activity of secretory acid sphingomyelinase (S-ASM) and routine blood parameters were determined in the serum of patients with current (unmedicated n = 63, medicated n = 66) and remitted (n = 39) MDD and healthy subjects (n = 61). Depression severity and anxiety and their 3-weeks prospective course of treatment were assessed by psychometric inventories. S-ASM activity was not different between the four groups, did not decrease during treatment, and was not lower in individuals taking medication that functionally inhibited ASM. However, S-ASM correlated positively with depression severity only in remitted patients. High enzyme activity at inclusion predicted milder clinician-evaluated and self-rated depression severity (HAM-D, MADRS, BDI-II) and state anxiety at follow-up, and was related to stronger improvement in these scores in medicated patients. S-ASM was strongly and contrariwise associated with serum lipids in unmedicated and medicated females. These findings contribute to a better understanding of the pathomechanisms underlying depression and the development of clinical strategies and biomarkers.
CRIS-Team WoS Importer:2019-07-30

Serial repetitive transcranial magnetic stimulation (rTMS) decreases BDNF serum levels in healthy male volunteers - Schaller, Gerd; Sperling, Wolfgang; Richter-Schmidinger, Tanja; Mühle, Christiane; Heberlein, Annemarie; Maihöfner, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of Neural Transmission, 2014)
Although repetitive transcranial magnetic stimulation (rTMS) is established in the treatment of depression, there is little knowledge about the underlying molecular mechanisms. In the last decade, the neurotrophic hypothesis of depression entailed a plethora of studies on the role of neurogenesis-associated factors in affective disorders and rTMS treatment. In the present study, we hypothesised a sham-controlled increase of peripheral brain-derived neurotrophic factor (BDNF) levels following serial rTMS stimulations in healthy individuals. We investigated the influence of a cycle of nine daily high-frequency (HF)-rTMS (25 Hz) stimulations over the left dorsolateral prefrontal cortex (DLPFC) on serum levels of BDNF in 44 young healthy male volunteers. BDNF serum concentrations were measured at baseline, on day 5 and on day 10. Overall, the statistical analyses showed that the active and sham group differed significantly regarding their responses of BDNF serum levels. Contrary to our expectations, there was a significant decrease of BDNF only during active treatment. Following the treatment period, significantly lower BDNF serum levels were quantified in the active group on day 10, when compared to the sham group. The participants' smoking status affected this effect. Our results suggest that serial HF-rTMS stimulations over the left DLPFC decrease serum BDNF levels in healthy male volunteers. This provides further evidence for an involvement of BDNF in clinical rTMS effects.
EVALuna2:23619

Serum lipids, leptin, and soluble leptin receptor in alcohol dependence: A cross-sectional and longitudinal study - Weinland, Christian; Tanovska, Petya; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Drug and Alcohol Dependence, 2020)
Objective: Alcohol dependence affects metabolic processes. Further research is needed to apply this knowledge clinically. In this study, possible differences in serum lipids and/or leptin activities between alcohol-dependent in-patients and healthy controls and possible associations with alcohol-related blood parameters and with prospective outcomes in alcohol dependence were assessed sex-specifically.
CRIS-Team WoS Importer:2020-05-08

Sex-Dependent Alcohol Instrumentalization Goals in Non-Addicted Alcohol Consumers versus Patients with Alcohol Use Disorder: Longitudinal Change and Outcome Prediction - Müller, Christian P.; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2021)
Background Alcohol can be instrumentalized to achieve goals that without the drug would either not be achievable or would be so only with considerably more workload. While an understanding of the neurobiological mechanisms of alcohol instrumentalization is emerging, little information is available concerning instrumentalization goals in controlled consumers and how these goals change during the development of an alcohol use disorder (AUD).
CRIS-Team WoS Importer:2021-03-12

Suicide after Discharge from psychiatric Institutions - Lenz, Bernd (Fortschritte der Neurologie - Psychiatrie, 2019)
CRIS-Team WoS Importer:2019-08-23

Sulphated dehydroepiandrosterone serum levels are reduced in women with alcohol use disorder and correlate negatively with craving: A sex-separated cross-sectional and longitudinal study - Weinland, Christian; Mühle, Christiane; von Zimmermann, Claudia; Kornhuber, Johannes; Lenz, Bernd (Addiction Biology, 2022)
Previous studies have established a role of sex hormones in alcohol use disorder (AUD).Only few clinical investigations with low numbers of patients with AUD have focused on the sulphated form of dehydroepiandrosterone (DHEA-S), despite its function as a neuromodulating sex steroid on receptors in the central nervous system (γ-aminobutyric acid type A, N-methyl-D-aspartate, sigma-1 receptors). DHEA-S serum levels were compared between 200 inpatients with AUD (44% women) admitted for withdrawal treatment and 240 healthy controls (45% women) and analysed longitudinally in patients from early abstinence (baseline) to a median of 5 days later. We also correlated DHEA-S levels with craving, liver enzyme activities, and prospective alcohol-related readmissions during a 24-month follow-up. DHEA-S concentrations were lower in female patients than in female healthy controls during baseline (70%) and decreased from baseline to follow-up in the female and male patients groups (down to: women, 92%; men, 76%). Baseline DHEA-S concentrations correlated with the total and obsessive subscales of the Obsessive–Compulsive Drinking Scale and with maximum visual analogue scale craving scores in female patients (Rho ≤ −0.240) and gamma-glutamyl transferase activity in female (Rho = −0.292) and male (Rho = −0.391) patients. DHEA-S did not significantly predict outcome. We found interactions with smoking behaviour and age. This is the first study based on large cohorts of inpatients with AUD undergoing a qualified detoxification treatment to provide sex-separated evidence for associations of DHEA-S serum concentrations with AUD and related phenotypes. The results stimulate further investigations whether DHEA-S directly influences alcohol craving building a basis to develop sex-sensitive prevention and treatment strategies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: AUD; craving; DHEA -S; relapse; sex hormones

TaKeTiNa Music Therapy for Outpatient Treatment of Depression: Study Protocol for a Randomized Clinical Trial - Behzad, Ali; Feldmann-Schulz, Christoph; Lenz, Bernd; Clarkson, Lucy; Ludwig, Celine; Luttenberger, Katharina; Völkl, Simon; Kornhuber, Johannes; Mühle, Christiane; von Zimmermann, Claudia (Journal of Clinical Medicine, 2024)
Background/Objectives: Depression is a prevalent and debilitating illness that significantly affects psychological and physical well-being. Apart from conventional therapies such as psychotherapy and medication, individuals with depression often lack opportunities for activities that are generally perceived as enjoyable, such as music, meditation, and arts, which have demonstrated therapeutic effectiveness. TaKeTiNa music therapy has been employed as a therapeutic intervention for more than two decades. However, there is a notable absence of well-designed clinical trials investigating its antidepressant effects, a gap we aim to address in our current study. Furthermore, shifts in the progression of depression may manifest both psychologically, by influencing emotional states, and physiologically, by leading to alterations in lipid and sphingolipid metabolism, cortisol levels, and immune system function. Our study seeks to analyze the impact of TaKeTiNa music therapy on both levels. Methods: This is a prospective monocentric randomized waitlist-controlled clinical trial. It investigates the influence of TaKeTiNa music therapy on patients with major depression in an outpatient setting. Therefore, interested persons are randomly assigned to two groups, an intervention group or a control group, after completing a screening procedure. The intervention group starts with an eight-week TaKeTiNa music therapy intervention. The waiting group receives the same therapy program after completing the follow-up period. Blood and saliva sampling as well as responses to questionnaires are obtained at specific time points. Discussion: Our study investigates the effects of TaKeTiNa music therapy, a non-pharmacological antidepressant treatment option, on depressive symptoms. We also address functional and causal immunological changes; hormonal changes, such as changes in cortisol levels; and metabolic changes, such as changes in serum lipids and sphingolipids, during the course of depression. We expect that this study will provide evidence to expand the range of treatment options available for depression.
CRIS-Team Scopus Importer:2024-05-24
Keywords: affective disorder; depression; immune system; music therapy; non-pharmacological therapy; randomized waitlist-controlled trial; translational

The androgen model of suicide completion - Lenz, Bernd; Röther, Mareike; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Tektas, Ozan Y.; Kornhuber, Johannes (Progress in Neurobiology, 2019)
Suicide is a devastating public health issue that imposes severe psychological, social, and economic burdens not only for the individuals but also for their relatives, friends, clinicians, and the general public. Among the different suicidal behaviors, suicide completion is the worst and the most relevant outcome. The knowledge of biological etiopathological mechanisms involved in suicide completion is limited. Hitherto, no objective markers, either alone or in combination, can reliably predict who will complete a suicide. However, such parameters are strongly needed to establish and optimize prediction and prevention. We introduce here a novel ideation-to-completion framework in suicide research and discuss the problems of studies aiming at identifying and validating clinically useful markers. The male gender is a specific risk factor for suicide, which suggests that androgen effects are implicated in the transition from suicidal ideation to suicide completion. We present multiple lines of direct and indirect evidence showing that both an increased prenatal androgen load (with subsequent permanent neuroadaptations) and increased adult androgen activity are involved in suicide completion. We also review data arguing that modifiable maternal behavioral traits during pregnancy contribute to the offspring's prenatal androgen load and increase the risk for suicide completion later in life. We conclude that in utero androgen exposure and adult androgen levels facilitate suicide completion in an synergistic manner. The androgen model of suicide completion provides the basis for the development of novel predictive and preventive strategies in the future.
EVALuna2:211632

The cortical Amyloid Burden correlates positively with subjective Loneliness in non-demented elderly People - Lenz, Bernd (Fortschritte der Neurologie - Psychiatrie, 2017)
EVALuna2:33579

The influence of prenatal risks on attachment, emotion regulation and emotional and behavioral problems in middle childhood: A prospective longitudinal study - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

TNF-? and IL-6 serum levels: neurobiological markers of alcohol consumption in alcohol-dependent patients? - Heberlein, Annemarie; Kaeser, Marius; Lichtinghagen, Ralf; Rhein, Mathias; Lenz, Bernd; Kornhuber, Johannes; Bleich, Stefan; Hillemacher, Thomas (Alcohol, 2014)
We investigated the serum levels of IL-6 and TNF-? in 30 male alcohol-dependent patients during withdrawal (day 1, 7, and 14) and compared them with the levels obtained from 18 healthy male controls. IL-6 (day 1: T = 2,593, p = 0.013; day 7: T = 2,315, p = 0.037; day 14: T = 1,650, p = 0.112) serum levels were significantly increased at the beginning of alcohol withdrawal. TNF-? (T = 3,202, p = 0.03) serum levels were significantly elevated in the patients' group during the whole period of withdrawal. IL-6 serum levels decreased significantly during withdrawal (F = 16.507, p < 0.001), whereas TNF-? levels did not change significantly (day 1-14). IL-6 serum levels were directly associated with alcohol consumption (r = 0.392, p = 0.047) on day 1. Moreover, the IL-6 serum levels were associated with alcohol craving (PACS total score day 1: r = -0.417, p = 0.022, the score of the obsessive subscale of the OCDS on day 14 [r = -0.549, p = 0.022]), depression (r = -0.507, p = 0.005), and trait anxiety (r = -0.674, p < 0.001) on day 1. We found an association with the duration of active drinking following the last period of abstinence and the TNF-? serum levels (day 1:r = 0.354, p = 0.009; day 7: r = 0.323, p = 0.022; day 14: r = 0.303, p = 0.034) as well as an association with the severity of alcohol dependence measured by the SESA scale (r = 0.454, p = 0.015). Moreover, we found a significant association between the BDNF serum levels and the TNF-? serum levels (r = -0.426, p = 0.021). Our results support an association between alterations in TNF-? and IL-6 serum levels and alcohol consumption.
EVALuna2:23652